Conditional survival analysis in Korean patients with gastric cancer undergoing curative gastrectomy. Issue 1 (December 2015) - Lee, Jin; Ali, Bandar; Yoo, Han; Park, Cho; Song, Kyo
Abstract Background Conditional survival (CS) measures the probability that patients will survive an additional number of years given that they have already survived for a certain period of time. Methods In total, 2935 gastric cancer patients who had undergone curative gastrectomy between 1995 and 2011 were enrolled. The Cox proportional hazard regression model was used to evaluate the factors associated with overall survival (OS). Three-year CS estimates at 't' years after surgery were calculated as follows: CS(t) = S(t + 3)/S(t). Results The 1-, 2-, 3-, 4- and 5-year OS rates of the 2935 patients were 96.6 %, 92.0 %, 88.7 %, 85.6 and 82.7 %, respectively. The probability of surviving an additional 3 years on the condition of having already survived 1, 2, 3, 4 and 5 years after surgery were 88.6 %, 89.9 %, 91.0 %, 92.2 % and 93.2 %, respectively. Patients with a higher risk at baseline showed a greater increase in CS over time. Conclusions CS estimates provide important information about dynamic prognostic changes over time for Korean gastric cancer patients, and as such, can be used to guide long-term follow-up strategies.